Cat-a-wall - Grindley, Sally; Allwright, Deborah (London : A&C BLack, 2008)
Scruff thinks he is the most wonderful singer in the world. It's a pity his owners don't feel the same. But when scruff sets out to look for someone who enjoys hearing him sing, he is not prepared for what he finds.
Keywords: Cats -- Fiction; Singing -- Fiction